A Bibliography of Cuneiform Tablet Editions in United States Colleges and Universities through 2020. (29th March 2021) - Mohr, Sara
This dataset contains bibliographic data of publications containing scholarly editions in any language of cuneiform tablets in small collections of cuneiform objects (typically 5–20 objects) in United States colleges and universities, current through 2020. These collections include a variety of ancient text forms, including but not limited to economic documents, letters, cylinder seals, and large reliefs. The dataset is stored on the JOHD Dataverse Repository. The data was compiled as part of a larger project to map the collections of cuneiform in the United States for the purposes of increasing access. Reuse potential includes its use as a reference tool for the history of Assyriology, for producing scholarship around the objects in these collections, for historical bibliometric data, and for the reconstruction of ancient cuneiform corpora throughout the United States.